The Power of Sholawat: Music, Devotion, and Islamic Authority in Indonesia - Agha, Albert Nasser (Tebuireng: Journal of Islamic Studies and Society, 2025)
This article examines the interplay between religious authority and culture through the lens of sholawat in Indonesia—an event characterized by a fusion of musical and oratorical performances among devout Muslims. Drawing on fieldwork conducted in Yogyakarta, Central Java, I demonstrate how institutions and individuals strategically employ artistic expression to mediate both contemporary and historical religious discourses in public life. By exploring sholawat, one gains insight into a facet of modern Islam that is highly accessible, festive, and inclusive of a broad and diverse audience. Within these performances, religious authority is subtly legitimized through what I term a “religious culture of play” embedded in everyday life. Employing Paul Ricoeur’s analysis of enunciative and institutional authority alongside Hans-Georg Gadamer's concept of play, I examine how and why Indonesia’s distinctive Islamic tradition—commonly known as Islam Nusantara—offers a compelling model for the contemporary Islamic world. The article begins by outlining the structure of a sholawat event and the key individuals and institutions involved in its organization. It then engages with theoretical perspectives on religious authority, considering their relevance within Indonesia’s internal Islamic dynamics. Finally, I explore the role of play as an essential element of sholawat as a form of religious art.